A new fungus-mediated RNAi method established and used to study the fatty acid and retinol binding protein function of the plant-parasitic nematode Aphelenchoides besseyi. Issue 10 (3rd October 2021) - Ding, Shanwen; Wang, Dongwei; Xu, Chunling; Yang, Sihua; Cheng, Xi; Peng, Xiaofang; Chen, Chun; Xie, Hui
ABSTRACT: RNA interference (RNAi) is a powerful tool for gene functional analysis of plant-parasitic nematodes (PPNs). RNAi involving soaking in a dsRNA solution and in planta methods is commonly applied in the study of gene function in PPNs. However, certain problems restrict the application of these methods. Therefore, more convenient and effective RNAi methods need to be established for different PPNs according to their biological characteristics. In this study, the fatty acid and retinoid binding protein genes ( Ab-far-1, Ab-far-4, and combinatorial Ab-far-1 and Ab-far-4 ) of the rice white tip nematode (RWTN), Aphelenchoides besseyi, were used as target genes to construct a fungal RNAi vector, and the Ab-far-n dsRNA transgenic Botrytis cinerea (ARTB n ) were generated using Agrobacterium -mediated transformation technology. After RWTN feeding on ARTB n, the expression of Ab-far-1 and Ab-far-4 in the nematodes was efficiently silenced, and the reproduction and pathogenicity of the nematodes were clearly inhibited. The Ab-far-1 and Ab-far-4 co-RNAi effects were better than the effects when each gene was individually targeted with RNAi. Additionally, the RNAi induced when RWTNs fed on ARTB 1 were persistent and heritable. Thus, a new method of fungus-mediated RNAi was established for fungivorous PPNs and was verified as effective and applicable to the study of nematode gene function. This technique will remove the technological bottlenecks and provide a new method to studying the multiple genes with polygene co-RNAi in fungivorous PPNs. This study also provides a theoretical basis and new thought for further study of the gene function in PPNs. Abbreviations: FAR(Fatty acid and retinol-binding proteins); RWTN (The rice white tip nematode, Aphelenchoides besseyi); Ab-far-n (Fatty acid and retinol binding protein gene of A. besseyi) ; ARTB 1 ( Ab-far-1 hpRNA transgenic Botrytis cinerea ); ARTB 4 ( Ab-far-4 hpRNA transgenic Botrytis cinerea ); ARTB 1 / 4 (combinatorial Ab-far-1 and Ab-far-4 hpRNA transgenic B. cinerea ); EVTB (Empty vector transgenic B. cinerea ); GRTB (eGFP hpRNA transgenic B. cinerea ); WTB (Wild-type B. cinerea ).